Investigation of the Route of Absorption of Lipid and Sugar Modified Leu- Enkephalin Analogues and Their Enzymatic Stability Using the Caco-2 Cell Monolayer System - Wu, Sherry; Campbell, Christopher; Koda, Yasuko; Blanchfield, Joanne T.; Toth, Istvan (Medicinal Chemistry, 2006)
It has been demonstrated that conjugation of lipoamino acids or glucose units to the endogenous opioid peptide, Leu-enkephalin can significantly improve the peptide's metabolic stability and absorption across biological barriers. The purpose of this study was to investigate the possible involvement of specific carrier proteins in the absorption of these peptide conjugates. A series of lipo- glycol- and liposaccharide peptide conjugates were synthesised and examined using the Caco-2 monolayer assay for evidence of interaction with the human H+-coupled oligopeptide transporter (hPepT1), glucose transporters and the multidrug resistance efflux pump, p-glycoprotein. The investigation involved determining the apparent permeability of each compound in the absence of any inhibitors and comparing this to the apparent permeabilities of each compound in the presence of glycylsarcosine, glucose or vinblastine, respective inhibitors of the above mentioned transporters. None of the peptide conjugates were found to be substrates for p-glycoprotein. Of the six peptide conjugates examined, only the C-terminus glucose conjugate of Leu-enkephalin (Enk-glu) showed evidence of transport by both glucose transporters and hPepT1. In contrast, N-terminus conjugation of both lipids and sugars appeared to provide the greatest protection against enzymatic degradation.
Keywords: drug delivery liposaccharides